United Learning (A) - Diermeier, Daniel (SAGE Knowledge. Cases., 2017)
United Learning is a family-owned leader in the K-12 supplementary teaching material market. In January 2001, United Learning realized that sales for one of its flagship products, a drug and prevention program, were rapidly deteriorating because the program was not mentioned on a recently released U.S. Department of Education list of recommended products. United Learning must decide on which action to take: regain sales or focus on its other educational products--which are also threatened by changes in the regulatory environment.